2017
DOI: 10.2147/ijn.s130397
|View full text |Cite
|
Sign up to set email alerts
|

In situ green synthesis of antimicrobial carboxymethyl chitosan–nanosilver hybrids with controlled silver release

Abstract: In order to fabricate antimicrobial carboxymethyl chitosan–nanosilver (CMC-Ag) hybrids with controlled silver release, this study demonstrated comparable formation via three synthetic protocols: 1) carboxymethyl chitosan (CMC) and glucose (adding glucose after AgNO 3 ), 2) CMC and glucose (adding glucose before AgNO 3 ), and 3) CMC only. Under principles of green chemistry, the synthesis was conducted in an aqueous medium exposed to microwave irradiation for 10 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Additionally, the peak at 1329 cm –1 is ascribed to C–OH stretching vibration . The two peaks at 1420 and 1602 cm –1 are assigned to symmetric and asymmetric stretching vibrations of −COOH, respectively . Moreover, the peak at 2932 cm –1 is attributed to C–H stretching and the peak at 3447 cm –1 is assigned to the overlapping of N–H and O–H stretching vibrations.…”
Section: Results and Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Additionally, the peak at 1329 cm –1 is ascribed to C–OH stretching vibration . The two peaks at 1420 and 1602 cm –1 are assigned to symmetric and asymmetric stretching vibrations of −COOH, respectively . Moreover, the peak at 2932 cm –1 is attributed to C–H stretching and the peak at 3447 cm –1 is assigned to the overlapping of N–H and O–H stretching vibrations.…”
Section: Results and Discussionmentioning
confidence: 73%
“…Also, the nZVI@nBent–CMC composite pattern shows this distinctive peak of nZVI without the appearance any peaks for other iron oxides, which could be attributed to the complete coverage of nZVI with nBent–CMC that protects its surface from oxidation . Furthermore, nBent was recognized by the appearance of the distinguishing peaks at 2θ = 35 and 61.8°, whereas CMC was identified by the occurrence of a characteristic peak at 2θ = 21.1° . Thus, XRD patterns show the main components quite evidently, which confirms that the nZVI@nBent–CMC composite has been successfully synthesized.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The analysis of the IR data of the composites suggest that Ag NPs and CNF/PVA form stable composite via electrostatic interaction between negatively charged carboxylic groups and positively charged groups on the Ag NPs. Similar results were observed previously in other inorganic nanomaterials and cellulose composites …”
Section: Resultsmentioning
confidence: 99%
“…In vitro release experiments showed that CA/SA/Ch NPs had the function of sustained release, indicating that SA/Ch NPs can be used as a promising carrier for CA [ 142 ]. Antimicrobial carboxymethyl chitosan-nanosilver (CMC-Ag) hybrids with controlled silver release was fabricated by Huang et al [ 143 ]. Under principles of green chemistry, the synthesis was conducted in an aqueous medium exposed to microwave irradiation for 10 min with non-toxic chemicals.…”
Section: Green Synthesis Of Chitin/chitosan/chitin and Chitosan Npsmentioning
confidence: 99%